186k views
2 votes
Can anyone solve this....

7((2-2y)/(5))+3y=6

I know y=16, but I was wondering how to get to that point???

User Ifaour
by
5.5k points

2 Answers

1 vote
7((2 - 2y) / (5)) + 3y = 6

7(.4 - .4y) + 3y = 6

2.8 - 2.8y + 3y = 6

Combining like terms...

2.8 + .2y = 6

0.2y = 3.2

And that's how you get 16. Things get a bit easier if you convert your fractions into decimals instead of working with all that clutter.
User Peterlandis
by
5.9k points
4 votes
First you would do distributive property... multiply the seven by two and negative 2y. This would make the equation 14-14y/5+3y=6

Now we're going to combine like terms...

-14y and 3y gets you -11y

14/5 gets you 2.8

New equation is -11y+ 2.8 = 6
Subtract 2.8 form both sides...

New equation is -11y = 3.2

Divide both sides by -11

y= a repeating decimal...how did you get 16?

If you want to know how you got 16 plug 16 back in for "y" and see if the equation is true or false.
User Extricate
by
5.7k points